1987
DOI: 10.1002/j.1460-2075.1987.tb04829.x
|View full text |Cite
|
Sign up to set email alerts
|

Host-specific regulation of nodulation genes in Rhizobium is mediated by a plant-signal, interacting with the nodD gene product

Abstract: We have identified a nodD gene from the wide host‐range Rhizobium strain MPIK3030 (termed nodD1) which is essential for nodulation on Macroptilium atropurpureum (siratro). Experiments with nodA–lacZ gene fusions demonstrate that the MPIK3030 nodD1 regulates expression of the nodABC genes. Additionally, we used nodC–lacZ fusions of Rhizobium meliloti to show that the MPIK3030 nodD1 gene induces expression of these fusions by interacting with plant factors from siratro and from the non‐host Medicago sativa (alfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
125
0
3

Year Published

1987
1987
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(131 citation statements)
references
References 39 publications
3
125
0
3
Order By: Relevance
“…Because these vir gene inducers have no apparent function in the physiology ofAgrobacterium, except as inducers of vir genes, it seems likely that the differences in the VirA protein in the various strains relate to differences in their ability to interact with the phenolic compound directly rather than with a protein that has bound the phenolic compound. A similar conclusion has been reached for nod gene induction in Rhizobium, also based on genetic data (9,10).…”
Section: Discussionsupporting
confidence: 80%
“…Because these vir gene inducers have no apparent function in the physiology ofAgrobacterium, except as inducers of vir genes, it seems likely that the differences in the VirA protein in the various strains relate to differences in their ability to interact with the phenolic compound directly rather than with a protein that has bound the phenolic compound. A similar conclusion has been reached for nod gene induction in Rhizobium, also based on genetic data (9,10).…”
Section: Discussionsupporting
confidence: 80%
“…Recently, it has been reported that different nodD genes show different inducer specificities (34). It might be expected that acquisition of a B. japonicum nodD would broaden the The results shown here indicate that genes involved in the earliest steps in nodule formation are not fully expressed in the culture conditions traditionally used in laboratory studies of the B. japonicum/soybean symbiosis and in the preparation of commercial inocula for use in agriculture.…”
Section: "'Iscussionmentioning
confidence: 73%
“…nodD is a regulatory gene that is constitutively expressed and is required for induction of other nod genes (32)(33)(34). Recently, it has been reported that different nodD genes show different inducer specificities (34).…”
Section: "'Iscussionmentioning
confidence: 99%
“…homology (40) (9)(10)(11)(12)(13)18), which are involved in host-range specificity at the legume genus level.…”
Section: Resultsmentioning
confidence: 99%
“…Host-specific nodulation (hsn) determinants have also been reported in Rhizobium melioti (10), Rhizobium leguminosarum biovars trifolii (11) and viceae (12), in the broad host-range Rhizobium sp. strain MPIK3030 (13), and in B. japonicum (7,14,15).…”
mentioning
confidence: 95%